Denmark : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
Denmark showed strong performance owing to its stability-oriented policies, high growth rates, and low unemployment. Executive Directors noted that the Danish flexicurity model has worked well, and stressed the need for prudent fiscal policies. Executive Directors welcomed the outcome of the Financial Sector Assessment Program (FSAP), which found the Danish financial system to be healthy and well supervised. They underscored the importance of strengthening the budget, its stress-testing capacity and cross-border supervision, welcomed the fixed-exchange rate policy, and agreed that with the Welfare Agreement, the Danish economy can face future challenges.